2021
DOI: 10.3389/fpsyg.2021.514886
|View full text |Cite
|
Sign up to set email alerts
|

Hungarian Structural Focus: Accessibility to Focused Elements and Their Alternatives in Working Memory and Delayed Recognition Memory

Abstract: The present work investigates the memory accessibility of linguistically focused elements and the representation of the alternatives for these elements (i.e., their possible replacements) in Working Memory (WM) and in delayed recognition memory in the case of the Hungarian pre-verbal focus construction (preVf). In two probe recognition experiments we presented preVf and corresponding focusless neutral sentences embedded in five-sentence stories. Stories were followed by the presentation of sentence probes in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
(145 reference statements)
1
2
0
Order By: Relevance
“…In language comprehension, Gotzner et al (2016) observed for German that the recognition of mentioned alternatives is harder when focus is marked with particles. Calhoun et al (2023) report similar findings for Samoan, where focus is marked by cleft-like structures, as do Káldi et al (2021) for the preverbal focus construction in Hungarian. By contrast, Yan and Calhoun (2020) found that prosodic focus marking in Mandarin Chinese and in English, facilitated the decision that an alternative had not been mentioned.…”
Section: Discussionsupporting
confidence: 58%
“…In language comprehension, Gotzner et al (2016) observed for German that the recognition of mentioned alternatives is harder when focus is marked with particles. Calhoun et al (2023) report similar findings for Samoan, where focus is marked by cleft-like structures, as do Káldi et al (2021) for the preverbal focus construction in Hungarian. By contrast, Yan and Calhoun (2020) found that prosodic focus marking in Mandarin Chinese and in English, facilitated the decision that an alternative had not been mentioned.…”
Section: Discussionsupporting
confidence: 58%
“…As far as response times were concerned, the authors report no effects of probe type or sentence type. Overall, the study of Káldi et al (2021) suggests that the research on the improved memory representation of alternatives can be extended to languages with syntactically marked focus. However, their results are largely inconclusive.…”
mentioning
confidence: 99%
“…However, languages can also use syntactic means as their primary way of focus marking (Zimmermann and Onea, 2011).There have only been a few studies examining focus alternative processing in languages that primarily use syntactic means to mark focus. Studying Hungarian, Káldi et al (2021) also examined the memory representation of the focused element and of alternatives and provided evidence suggesting that the recall of the focused element was facilitated. This was in line with the previous literature.…”
mentioning
confidence: 99%